2011
DOI: 10.1007/978-3-642-21640-4_26
|View full text |Cite
|
Sign up to set email alerts
|

A Metamodelling Approach for i* Model Translations

Abstract: The i* (i-star) framework has been widely adopted by the information systems community. Since the time it was proposed, different variations have arisen. Some of them just propose slight changes in the language definition, whilst others introduce constructs for particular usages. This flexibility is one of the reasons that makes i* attractive, but it has as counterpart the impossibility of automatically porting i* models from one context of use to another. This lack of interoperability makes difficult to build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
0
11
0
2
Order By: Relevance
“…At a first sight, this work may seem to contradict somehow some of our previous work on the construction of an i* metamodel [15][5] [16] [14]. In these works, we advocate for an i* metamodel general enough to host most of the proposed variants of i*.…”
Section: Ic4mentioning
confidence: 73%
See 2 more Smart Citations
“…At a first sight, this work may seem to contradict somehow some of our previous work on the construction of an i* metamodel [15][5] [16] [14]. In these works, we advocate for an i* metamodel general enough to host most of the proposed variants of i*.…”
Section: Ic4mentioning
confidence: 73%
“…Several contributions exist that propose metamodels for i* with different purposes: 1) metamodels for particular i* variants like GRL's [12] and Tropos' [13]; 2) metamodels for supporting model interoperability [14]; 3) metamodels for providing a reference framework [15][16]; 4) metamodels as the basis for tool construction [17].…”
Section: Sources Of Our Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if it seems a low number, it has to be considered that the core community of researchers is not too big. As an indicator, we explored the literature review presented in [18] and counted 196 authors contributing to the 146 papers found; thus the survey's population was about the 10% of this core community of authors.…”
Section: A Community Perception On Specialization From I* Researchersmentioning
confidence: 99%
“…On the contrary, our work stems from the idea that preserving as far as possible the working environment of the stakeholders involved in organizations which aim to cooperate is more realistic. This leads us to propose a translator between different kinds of existing RE models that follows, in a broader way, the principle of Cares and Franch [12]. These ones have defined a "super meta-model" hosting identified variations of i* and implementing a semantic preservation oriented translation algorithm between these different variations.…”
Section: Introductionmentioning
confidence: 99%